Optical Density Assay to Determine the Sensitivity of Globisporangium and Pythium Isolates to Mefenoxam - Umbrin Ilyas; Lindsey J. du Toit; Mary Ruth McDonald (PhytoFrontiers)
Several species of Globisporangium and Pythium cause cavity spot of carrot. Disease management in conventional production relies primarily on application of the fungicide mefenoxam. Growers’ reports in Ontario, Canada, of severe cavity spot, even when using mefenoxam applications, suggest that mefenoxam resistance may be prevalent in pathogen populations in this region. The objectives of the study were to develop a rapid and accurate optical density (OD) assay to assess mefenoxam sensitivity of 188 isolates of Globisporangium and Pythium species collected from 13 carrot fields in Ontario from 2020 to 2023. The isolates belonged to seven species: G. intermedium, G. irregulare, G. rostratifingens, G. sylvaticum, G. ultimum, G. violae, and P. sulcatum. The OD was measured at 600 nm in broth amended with different concentrations of mefenoxam, with OD readings at nine positions per well in a 96-well plate. The OD assay was validated by comparing half maximal effective concentration values with a standard fungicide-amended agar medium assay using 20 representative isolates. There was a significant linear relationship (R2 = 0.97, P < 0.0001) between the two assays. Of the 188 isolates tested, 24% exhibited <60% inhibition of mycelial growth at 5 μg ml−1 mefenoxam, 50% were inhibited by >60% at 5 μg ml−1, 19% were inhibited by >60% at 1 μg ml−1, and 7% were inhibited by >60% even at 0.1 μg ml−1. The OD assay proved to be efficient, rapid, and accurate for monitoring the mefenoxam sensitivity of these oomycetes. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.